Rancang Bangun Sistem Informasi Perencanaan Persediaan Obat Dengan Metode Winter Pada Dinas Kesehatan Kota Surabaya - Alfarisyi, Moch.; Sulistiowati, Sulis; Maulana, Yoppy Mirza (Jurnal JSIKA, 2014)
Dinas Kesehatan Surabaya is a government agency which responsible for public health area. Dinas Kesehatan has pharmacy division that has responsibility to implement Make-to-Stock strategy in case for supplying medical items. Dinas Kesehatan doesnât Â haveÂ  an accurate inventory planning which may cause over stock or stock out. To overcome this problem, we propose a solution by build an application that can analyze demands data pattern then generate data trend which suitable for the condition. It founds that the data provided has seasonal trend which can Â be forecast using Winter method. After implementing this solution, Dinas Kesehatan can reduce inventory into optimal condition which has not much difference compared with real condition approach on November and December. This application has Mean Percentage Error of 26% from forecast result using winter forcast.